MATHEMATICS LEARNING STRATEGIES FOR ELEMENTARY SCHOOL STUDENTS DURING THE COVID-19 PANDEMIC - Wati Asriningsih Pranoto; Karno Diantoro; Edy Wihardjo; Juni Susanti Banurea; Fitri Hidayati (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
This study aims to determine mathematics learning strategies for elementary school students during the Covid-19 Pandemic and determine the supporting and inhibiting factors in online learning. This research uses a qualitative descriptive method by describing mathematics learning strategies during the Covid-19 Pandemic. The results showed that mathematics teachers had used various learning strategies to strive for the learning process to be carried out during the Covid-19 Pandemic. These learning strategies are Online learning, Home visits in high grades and direct learning strategies, and Study Clubs at low rates. They are supporting and inhibiting factors in mathematics learning during the  Covid-19 Pandemic, namely (1) supporting factors in online learning, namely the existence of mobile phones as a medium that supports learning, the existence of quotas, the existence of book facilities from schools, and the existence of applications that facilitate us in teaching and learning activities online; and (2) inhibiting factors. Namely, the implementation of Online learning in mathematics learning is less conducive, it is difficult to measure learning achievement, and it is difficult to ascertain whether it is purely the result of student work and media problems such as not all students having Android phones or laptops and internet quota, there is signal interference or complex signals, cannot meet face to face which causes parents and students to lack understanding of the explanation of the material presented,  It is challenging to do the questions given and less enthusiastic in following the process in online learning. The results of this research were then shown through service activities at SDN 174 Palembang.